Strengthening Msme Business Owners, Village Credit Institutions (Lpds) In Bali, And The Indonesia Deposit Insurance Corporation (LPS) Through A Digital Ecosystem - Adrid Indaryanto; Dadang Hermawan; Ismoyo S. Soemarlan; Karina Putri Alamanda; Abu Siri (Bajang Institute, 2026)
The development of digital ecosystems has become increasingly essential for the sustainability and growth of Micro, Small, and Medium Enterprises (MSMEs), enabling businesses to expand market access and interact with consumers without spatial and temporal limitations. In Bali, MSME development business owner is closely linked to the presence of local financial institutions, particularly Village Credit Institutions (LPD), which play a strategic role in providing accessible financial services at the community level. At the same time, maintaining financial system stability is crucial, with deposit insurance serving as an important instrument to enhance public trust. The Indonesia Deposit Insurance Corporation (LPS) plays a key role in guaranteeing public deposits; however, not all LPDs are currently integrated into this system. This condition creates potential risks related to depositor protection and financial security, especially for MSMEs that rely on local financial institutions. This study aims to analyze the influence of digital ecosystems on MSME development business owner self efficacy, examine the role of LPDs in supporting MSMEs, and evaluate the impact of deposit insurance on public trust and financial system stability. In addition, this study highlights the importance of resilience in the digital financial ecosystem, emphasizing the capacity of MSMEs and local financial institutions to adapt to economic uncertainty, technological change, and financial risks. Furthermore, this study seeks to explore strategies for integrating LPDs into the LPS system to strengthen financial security and promote a more stable and inclusive financial system at the local level with the involvement of MSMES business owner self-efficacy